Innovation Challenges in Malaysia SME Biotechnology - Lai, Tuck Keong (2013)
The study was to find out the supporting elements that lead to innovation in Malaysia SME biotechnology firms. The context of this study was to understand the collaboration process that lead to better innovation for their product and service development. The results is to assist potential new start-up to navigate Malaysia biotechnology landscape as a lessons learned and what it takes to be successful in biotechnology investment. There are four settings that author was trying to uncover like collaboration in general, collaboration process, innovation process and critical success factors in collaboration. The study was undertaken to learn the lessons of what assist in their new product development. As a result of this study, the author uncovered that university, hospital and Research Institute are the collaborating partners for both participating firms in this study. Customer and supplier are playing a mild role in their success of innovation. Strategic alliance in term of marketing and commercialisation did not really help them. Project management, project manager and other factors made a success in their collaboration with external linkages. The author divided the critical success factors into five phases with each phase consists of factors that assist them in better collaborating. Overall, managing expectations, relationships and overall costs are important elements in collaborating for innovation.